Corona Discharge Detection and Confirmation Method Using Ultraviolet Camera - Choi, Dong-Hwan; Kim, Jae-Jin; Han, Ga-Ram; Park, Gi-Man; Jeon, Jeong-Chay; Bang, Jun-Ho; Ryu, In-Ho (International Journal of Engineering and Technology, 2018)
Background/Objectives: It is very difficult to detect and identify insulation defects in high-voltage systems using ultraviolet (UV) corona cameras. This paper describes the effect of measurement distance and UV camera type and gain on photon count.Methods/Statistical analysis: Experiments were carried out using two types of equipment (Superb and UVolle) manufactured by OFIL. As a result, we confirmed that the number of photons varies depending on the type, gain, and measurement distance of a UV camera.Findings: It is difficult to judge corona count value and abnormality of electric equipment only with measurement of corona in the equipment. With consideration of various factors other than simple corona count value and visual inspection, it is possible to decide whether there is defect or not.Improvements/Applications: In order to minimize errors in inspection and diagnosis in the field, we have proposed the UV corona determination criteria and implemented the applicable work process in the field.Â Â